Substitution-Inert Polynuclear Platinum Complexes Inhibit Reverse Transcription Preferentially in RNA Triplex-Forming Templates - Malina, Jaroslav; Farrell, Nicholas P; Brabec, Viktor (Inorganic chemistry, 2020)
RNA triplexes are significant tertiary structure motifs that are found in many functional RNAs. Hence, small molecules capable of recognition, binding, and stabilization of the triple-helical RNA structures are emerging as attractive potential molecular biology tools and therapeutic agents. Here, we utilize methods of molecular biology and biophysics to study the interactions of a series of antitumor substitution-inert polynuclear platinum complexes (SI-PPCs) with triple-helical RNA structures. We show that SI-PPCs recognize and stabilize RNA triplexes and inhibit reverse transcription preferentially in the RNA template prone to the triplex formation. These so far unexplored properties of SI-PPCs suggest that the targeting of triple-stranded regions in RNA might contribute to the biological effects of SI-PPCs.
Keywords: Platinum; konformace nukleové kyseliny; platina; Base Sequence; Coordination Complexes; Antineoplastic Agents; protinádorové látky; komplexní sloučeniny; Nucleic Acid Conformation; RNA; Reverse Transcription; sekvence nukleotidů; reverzní transkripce